Polskie specjalne strefy ekonomiczne w kontekście uregulowań prawnych po akcesji do Unii Europejskiej - Golonka, Tadeusz Piotr (Polish Special Economic Zones in the Context of Law Regulation after the Accession to the European Union, 2006)
This research shows an origin and a goal of special economic zones as an instrument of regions development, a fight with unemployment and support of investments. According to the accession of Poland to the European Union it was necessary to adjust Polish law in economic functioning of the zones to the rules of the European Union. Negotiations with the European Committee in this area lead to make "new" rules, presented in this research, regarding the help for investors. Although the rules limit some advantages of investments in the zones, the zones still remain very attractive instruments for investments without using direct resources from the national budget. An investor is able to use exemption from taxation only in case when he achieves expected effects in the form of the production beginning and the profit
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 231-239